Synthetization and numerical simulation of modified TiO2 for emerging flexible solar cell - Noorasid, Nur Syamimi (2023)
Dye-Sensitized solar cells (DSSCs) have attracted massive attention due to simple and low-cost fabrication process. In addition, it also suitable to be used for indoor application. Compared to commercially available silicon-based solar cells, which require complicated equipment, higher cost and heavy, flexible DSSCs are lighter in weight, thinner, and lower fabrication cost. In conventional DSSCs structure, anatase (TiO2) has been used as a photoanode layer. However, the TiO2 paste required a high-temperature treatment (> 450 °C) in order to obtain crystalline structure. The high-temperature process cannot be applicable to flexible DSSCs due to the flexible polymer substrates such as polyethylene terephthalate (PET) that are vulnerable to temperature, specifically below 150 °C. This study has conducted two analyses based on experiment and simulation. Titanium dioxide (TiO2) layer was synthesized and deposited with varying concentrations of titanium tetrapropoxide (TTIP) within the range of 0.3–0.7 M using the sol gel and spin coat method during deposition onto flexible substrates (ITO/PET). The impact of TTIP concentration on the electrical, structural, and optical properties has been studied. Ultraviolet visible (UV-Vis) spectrum demonstrates that the visible transmittance of the TiO2 layer lies between 10% to 23% and direct band gap energy within the range from 3.08 eV to 3.49 eV. X-ray diffraction (XRD) spectrum revealed that the average size of TiO2 crystallites ranged from 4.35 to 5.23 nm. According to the IV curve, the current density obtained within the range of 0.0011 µA to 0.0064 mA. Scanning electron microscopy (SEM) images for the concentration of 0.5 M achieved the most porosity structure than others. Thus, the layer of TiO2 with a concentration of 0.5 M TTIP demonstrates the ideal concentration of TTIP due to it high achievement of electrical, structural and optical properties. Next, the simulation carried out in this study used solar capacitance simulator (SCAPs) software and this simulation is based on the best band gap (3.2 eV) obtained from the experiment. Simulation part consists of 3 stages where all these stages use TiO2 as the main semiconductor material. The first stage is a simulation based on the DSSC structure. The simulation achieved efficiency of up to 8.14% by applying a 50 nm ultra-thin layer of TiO2 with a doping concentration of 1 × 1018 cm-3 and the results show that the four factors (thickness, temperature, doping concentration and defect density) analyzed are highly influential in improving the efficiency of DSSC. The next stage is a simulation based on the SSDSSC structure. This simulation examined the performance of SSDSSC with a variety of ETLs, including TiO2, ZnO, and SnO2. The simulation result indicates that the best ETL is TiO2, with maximum efficiency of 5.6%. The last stage is a simulation based on the structure of the PSC. In this simulation, it is found that each layer affects the performance of the PSC and proves that the optimization of each layer effectively improves the performance of the PSC. Remarkable results of the optimized structure have achieved impressive PSC efficiency 28.30% by the parametric analysis. This study will lead the path and can be a guidance to increase and enhancing the performance of generation photovoltaic cells.